Superficial Angiomyxomas Frequently Demonstrate Loss of Protein Kinase A Regulatory Subunit 1 Alpha Expression: Immunohistochemical Analysis of 29 Cases and Cutaneous Myxoid Neoplasms With Histopathologic Overlap. (February 2022) - Neumann, Neil M.; LeBoit, Philip E.; Cohen, Jarish N.
Abstract : Superficial angiomyxomas (SAMs) are benign cutaneous tumors that arise de novo and in the setting of the Carney complex (CC), an autosomal dominant disease with several cutaneous manifestations including lentigines and pigmented epithelioid melanocytomas. Although most SAM do not pose a diagnostic challenge, a subset can demonstrate histopathologic overlap with other myxoid tumors that arise in the skin and subcutis. Traditional immunohistochemical markers are of limited utility when discriminating SAM from histopathologic mimics. Since protein kinase A regulatory subunit 1 alpha ( PRKAR1A ) genetic alterations underlie most CC cases, we investigated whether SAM demonstrate loss of PRKAR1A protein expression by immunohistochemistry. In our series, 29 SAM, 26 myxofibrosarcoma, 5 myxoid dermatofibrosarcoma protuberans, 11 superficial acral fibromyxomas, and 18 digital mucous cysts were characterized. Of the 29 SAM examined in this study, 1 was associated with documented CC in a 5-year-old girl. SAM tended to arise in adults (mean 49.7 y; range: 5 to 87 y). Loss of PRKAR1A was seen in 55.2% of cases (16/29) and had a male predilection (87.5%, 12/16). PRKAR1A -inactivated SAM demonstrated significant nuclear enlargement (100%, 16/16 vs. 23.1%, 3/13), multinucleation (81.3%, 13/16 vs. 23.1%, 3/13), and presence of neutrophils (43.8%, 7/16 vs. 0%, 0/13). In contrast, PRKAR1A was retained in all cases of myxofibrosarcoma (100%, 26/26), myxoid dermatofibrosarcoma protuberans (100%, 5/5), superficial acral fibromyxomas (100%, 11/11), and digital mucous cyst (100%, 18/18). Taken together, PRKAR1A loss by immunohistochemistry can be used as an adjunctive assay to support the diagnosis of SAM given the high specificity of this staining pattern compared with histopathologic mimics.